Endogenous excretion of purine deIivatives and nitrogen in rams
A fasting nletabolism trial conducted using 8 adult Muzaffarnagari raIns (38.33Â±O.40 kg nlean body wt) to quantify the contribution of basal purine derivatives (PD) excretion to the total excretion of PD and to establish basal creatinine excretion and glomerular filtration rate (GFR). The ranlS fed a diet of vvheat straw and concentrate (50 : 50) at a fixed level of intake for 1 week prior to the experinlental period. The feed allothen reduced in steps (pre-fasting) within 6 days and subsequently, they were fasted for 6 days. The PD excretion decreased rapidly when the feed intake was reduced from a level equivalent to lnaintenance to 0 within 6 days and reached a 10 and relatively constant level during fasting. The excretion rates of creatinine remained almost similar up to 30% oftnaintenance feeding, but increased by further feed restriction. The relative contribution of allantoin to total PD (0/0) decreased froIn 84.1 (pre-fasting) to 78.3 during fasting, whereas the proportion (%) of uric acid and salvageable PD increased while fasting. Endogenous urinary nitrogen excretion during fasting was significantly lower than pre-fasting periods. The plasma concentration of PD declined significantly with feed restriction resulting in simultaneous reduction of renal clearance expressed in tefillS of tubular load. The pattern of change in plasma PD level during pre-fasting and fasting reflected that of urinary PD excretion. The total PD concentration (llffio1/L’) during fasting was 115.84Â±8.01. The reabsorption (%) of PD remained higher during fasting period as compared to pre-fasting. The nlean value of endogenous excretion (/-lffiollkgWO.75/d) of PD in urine was 217.40Â±7.29. Further elevated creatinine concentration of plasnla (,.onoll L) during fasting period resulted in variable GFR. Increased re-absorption (%) of PD during fasting indicates the inherent ability of sheep to conserve these compounds, for maintaining a constant level of endogenous PD excretion during fasting. From the results it is evident that the endogenous urinary excretion of PD (